Evolving viral and serological stages of Zika virus RNA-positive blood donors and estimation of incidence of infection during the 2016 Puerto Rican Zika epidemic: an observational cohort study. Issue 12 (December 2020) - Williamson, Phillip C; Biggerstaff, Brad J; Simmons, Graham; Stone, Mars; Winkelman, Val; Latoni, Gerardo; Alsina, Jose; Bakkour, Sonia; Newman, Christina; Pate, Lisa L; Galel, Susan A; Kleinman, Steven; et al.
Summary: Background: Puerto Rico began screening blood donations for Zika virus RNA with nucleic acid amplification tests (NAATs) on April 3, 2016, because of an emerging Zika virus outbreak. We followed up positive donors to assess the dynamics of viral and serological markers during the early stages of Zika virus infection and update the estimate of infection incidence in the Puerto Rican population during the outbreak. Methods: Blood donations from volunteer donors in Puerto Rico were screened for the presence of Zika virus RNA using the cobas Zika NAAT. Positive donations were further tested to confirm infection, estimate viral load, and identify Zika virus-specific IgM antibodies. Individuals with positive blood donations were invited to attend follow-up visits. Donations with confirmed infection (defined as detection of Zika virus RNA or IgM on additional testing of index or follow-up samples) were assessed for stage of infection according to Zika virus RNA detectability in simulated minipools, viral load, and Zika virus IgM status. A three-step process was used to estimate the mean duration of NAAT reactivity of Zika virus in human plasma from individuals identified pre-seroconversion with at least one follow up visit and to update the 2016 incidence estimate of Zika virus infection. Findings: Between April 3 and Dec 31, 2016, 53 112 blood donations were screened for Zika virus, of which 351 tested positive, 339 had confirmed infections, and 319 could be staged. Compared with IgM-positive index donations (n=110), IgM-negative index donations (n=209) had higher mean viral loads (1·1 × 10 6 vs 8·3 × 10 4 international units per mL) and were more likely to be detected in simulated minipools (93% [n=194] vs 26% [n=29]). The proportions of donations with confirmed infections that had viral RNA detected only in individual-donation NAATs (ie, not in simulated minipools) and were IgM positive increased as the epidemic evolved. The estimated mean duration of NAAT detectability in the 140 donors included in the follow-up study was 11·70 days (95% CI 10·06–14·36). Applying this detection period to the observed proportion of donations that were confirmed NAAT positive yielded a Zika virus seasonal incidence estimate of 21·1% (95% CI 18·1–24·1); 768 101 infections in a population of 3 638 773 in 2016. Interpretation: Characterisation of early Zika virus infection has implications for blood safety because infectivity of blood donations and utility of screening methods likely correlate with viral load and serological stage of infection. Our findings also have implications for diagnostic testing, public health surveillance, and epidemiology, and we estimate that around 21% of the Puerto Rican population was infected during the 2016 outbreak. Funding: Biomedical Advanced Research and Development Authority, National Heart, Lung, and Blood Institute.